Koeksistensi Perempuan Penopang Kehidupan di Pedesaan Demuk - Richa Meliza; Ibrahim Chalid; Iromi Ilham (Department of Anthropology, 2022)
Abstract: The phenomenon of the women life who support life in rural areas has reciprocity and adjustment in people's lives in terms of the domestic and public spheres. This must be done because of the weak point of view of the community on the culture and habits of women who are in these two domains. The purpose of this paper is to describe the lives of women who support life in rural areas that are different from women in urban areas, both from the domestic and public realms. This study used qualitative research methods. The data collection process was carried out through live In, observation, in-depth interviews (indept interviews), and the use of documentation studies. Women in rural areas have a stronger survival in continuing their lives, especially economic problems, although women's lives are limited in all access, they have a goal in the welfare of their families and communities by living on land as farmers. Village culture and customs that are still thick are not an obstacle in terms of working, if they are still in the realm of rural culture that is polite, respectful, please help and others. So it is not a problem for women in rural areas to work in both domestic and public spheres.Abtract: Fenomena kehidupan perempuan penopang kehidupan di daerah pedesaan memiliki timbal balik dan penyesuaian di dalam kehidupan masyarakat dari segi ranah domestik dan publik. Hal ini harus dilakukan bersebab lemahnya sudut pandang masyarakat terhadap budaya dan kebiasaan perempuan yang berada dalam kedua ranah tersebut. Tujuan dalam tulisan ini adalah untuk menggambarkan kehidupan terkait perempuan penopang kehidupan di daerah pedesaan yang berbeda dengan perempuan di daerah perkotaan, baik dari ranah domestik maupun publik. Penelitian ini menggunakan Metode penelitian kualitatif. Proses pengumpulan data dilakukan melalui Live In, observasi, wawancara mendalam (indept interview), dan penggunaan studi dokumentasi. Perempuan di daerah pedesaan mempunyai ketahanan hidup yang lebih kuat dalam meneruskan kehidupan terutama masalah ekonomi walaupun kehidupan para perempuan terbatas dalam segala akses, mereka memiliki tujuan dalam menyejahterakan keluarga dan masyarakat dengan cara bertanah hidup sebagai petani. Budaya dan adat istiadat pedesaan yang masih kental tidak menjadi kendala dalam hal bekerja, jika masih dalam ranah sesuai dengan budaya pedesaan yang santun, menghargai, tolong menolong dan lainnya. Sehingga tidak menjadi suatu permasalahan bagi perempuan di daerah pedesaan untuk bekerja dalam kedua ranah domestik dan publik.